Mobilitas Internasional Perempuan Sebagai Bentuk Diversifikasi Penghidupan Rumah Tangga Petani (Studi Kasus di Kecamatan Cikalong Kabupaten Tasikmalaya) - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa; Charina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Women's international mobility in agriculture-based rural areas represents a socio-economic transformation that reflects evolving gender roles within farming households. This study investigates the historical trajectory and underlying dynamics of female international migration as a livelihood diversification strategy in the Cikalong District, Tasikmalaya Regency, Indonesia. Utilizing a qualitative case study approach, data were collected through in-depth interviews with former migrant workers, labor brokers, local officials, and community leaders. Findings indicate that economic hardship was the primary driver of women's mobility. Initially confined to domestic roles, women began assuming the role of primary income earners by migrating abroad, predominantly as domestic workers. The success of early migrants catalyzed further migration, creating a self-reinforcing cycle. Beyond enhancing household economic resilience, this mobility reshaped intra-household gender relations. The study emphasizes the strategic role of women in rural livelihood systems and calls for inclusive, gender-sensitive rural development policies.